Analisis Aspek Operasional dan Manajemen Sumber Daya Insani pada Industri Konveksi Brand 57 Busana di Desa Dadirejo Kecamatan Tirto Kabupaten Pekalongan: Perspektif Studi Kelayakan Bisnis Syariah - Arny Juliyanti; Husni Awali (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2026)
The Operational Aspect in Islam emphasizes that production activities must benefit humanity or be related to meeting human needs. For example, the selection of raw materials should not come from haram sources, the production process should be free from activities prohibited by Sharia, production should not be excessive, and there should be no waste. The Islamic view on human resources emphasizes that all workers are huan beings, not robots or business tools. A A Business Feasibility Study refers to an analysis of a business plan, both prior to its implementation and once the business is operating on a regular basis. The aim of this study is to evaluate the operational aspects and human resource management within the feasibility study of the Islamic-based convection business, Brand 57 Busana Pekalongan. This research employs a qualitative approach. The data were collected through field research, which involves conducting the study directly at the site where the phenomena related to the research problem occur. The techniques applied for data collection include observation, interviews, and documentation The result of this study indicate that the Brand 57 Busana pekalongan is feasible in terms of operational and human resource management aspects from a Sharia businesss feasibility study perspective because it has chosen a strategic location, good product quality, adequate production capacity, and technology utilization. In addition, the brand 57 Busana Pekalongan convection is deemed permissible for operational production activities from an Islamic perspective, such as production activities based on Islamic values and Maqashid Syariah. In the implementation of human resources management, the Brand 57 Busana Pekalongan convention has implemented job descriptions, a Muslim work ethic, a fair and decent salary distribution system.